Left-Right Brain-Wide Asymmetry of Neuroanatomy in the Mouse Brain - Andrew Silberfeld; James M. Roe; Jacob Ellegood; Jason P. Lerch; Lily Qiu; Yongsoo Kim; Jong Gwan Lee; William D. Hopkins; Joanes Grandjean; Yangming Ou; Olivier Pourquié (NeuroImage)
Left-right asymmetry of the human brain is widespread through its anatomy and function. However, limited microscopic understanding of it exists, particularly for anatomical asymmetry where there are few well-established animal models. In humans, most brain regions show subtle, population-average regional asymmetries in thickness or surface area, alongside a macro-scale twisting called the cerebral petalia in which the right hemisphere protrudes past the left. Here, we ask whether neuroanatomical asymmetries can be observed in mice, leveraging 6 mouse neuroimaging cohorts from 5 different research groups (∼3,500 animals). We found an anterior-posterior pattern of volume asymmetry with anterior regions larger on the right and posterior regions larger on the left. This pattern appears driven by similar trends in surface area and positional asymmetries, with the results together indicating a small brain-wide twisting pattern, similar to the human cerebral petalia. Furthermore, the results show no apparent relationship to known functional asymmetries in mice, emphasizing the complexity of the structure-function relationship in brain asymmetry. Our results recapitulate and extend previous patterns of asymmetry from two published studies as well as capture well-established, bilateral male-female differences in the mouse brain as a positive control. By establishing a signature of anatomical brain asymmetry in mice, we aim to provide a foundation for future studies to probe the mechanistic underpinnings of brain asymmetry seen in humans – a feature of the brain with extremely limited understanding.